Network function heterogeneous redundancy deployment method based on immune algorithm - Qingqing ZHANG; Hongbo TANG; Wei YOU; Yingle LI (网络与信息安全学报)
Aiming at the problem that the existing security defense methods cannot resist many unknown vulnerabilities and backdoors in the network function virtualization platform, a mimic defense architecture for network function virtualization using mimic defense ideas was proposed, a heterogeneous redundant deployment method based on an immune algorithm for the construction of heterogeneous pools was proposed.Firstly, the degree of heterogeneity between heterogeneous entities was quantitatively evaluated in combination with the entropy value method, then the network function heterogeneous redundant deployment problem was constructed into a minimax problem with the optimization goal of maximizing the degree of heterogeneity between heterogeneous entities, and finally the immune algorithm was used to quickly solve the optimal deployment solution of network functions.Simulation results show that the proposed method can quickly converge to an optimal deployment scheme and ensure that the overall distribution of heterogeneity between heterogeneous bodies is at a high level, effectively increasing the diversity between heterogeneous bodies and improving the attacker's difficulty.